Pengaruh Information Quality, Information Quantity, dan Information Credibility Pada TikTok Terhadap Purchase Intention SAFF & Co. di Jakarta - Regina Amanda Kostianti; Fitriani Nur Utami (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Indonesia has experienced a significant increase in the number of internet users every year, which is utilized to access social media platforms like TikTok. SAFF & Co., a local Indonesian perfume brand, has leveraged TikTok to promote its products to reach a wider audience and generate e-WOM to boost purchasing intentions. This study aims to examine and analyze the simultaneous and partial effects of information quality, information quantity, and information credibility on purchase intention for SAFF & Co. in Jakarta through TikTok. A quantitative descriptive method was employed in this research. Data analysis was conducted using several techniques, including validity and reliability tests, descriptive analysis, classical assumption tests, multiple linear regression analysis, hypothesis testing both simultaneously and partially, and coefficient of determination. The results of the descriptive analysis showed that information quality, information quantity, and information credibility were in the good category. The hypothesis test results showed that information quality, information quantity, and information credibility have a simultaneous effect on purchase intention for SAFF & Co., and then information quality, information quantity, and information credibility have a partial effect on purchase intention. Based on the coefficient of determination, the influence of information quality, information quantity, and information credibility on purchase intention is 22.2%, and the remaining 77.8% is influenced by other variables not examined in this study.